Burden of trachoma in five counties of Eastern Equatoria state, South Sudan: Results from population-based surveys. - Angelia M Sanders; Aisha E P Stewart; Samuel Makoy; Joy J Chebet; Peter Magok; Aja Kuol; Carla Blauvelt; Richard Lako; John Rumunu; E Kelly Callahan; Scott D Nash (Public Library of Science (PLoS), 2017)
In order to decrease the prevalence of trachoma within the country, the Republic of South Sudan has implemented components of the SAFE strategy in various counties since 2001. Five counties in Eastern Equatoria state were surveyed in order to monitor progress of programmatic interventions and determine if additional rounds of Mass Drug Administration with azithromycin were needed.Five counties (Budi, Lafon, Kapoeta East, Kapoeta South and Kapoeta North) were surveyed from April to October 2015. A cross-sectional, multi-stage, cluster-random sampling was used. All present, consenting residents of selected households were examined for all clinical signs of trachoma using the World Health Organization (WHO) simplified grading system. 14,462 individuals from 3,446 households were surveyed. The prevalence of trachomatous inflammation-follicular (TF) in children ages one to nine years ranged from 17.4% (95% Confidence Interval (CI): 11.4%, 25.6%) in Budi county to 47.6%, (95% CI: 42.3%, 53.0%) in Kapoeta East county. Trachomatous trichiasis (TT) was also highly prevalent in those 15 years and older, ranging between 2.6% (95% CI: 1.6%, 4.0%) in Kapoeta South to 3.9% (95% CI: 2.4%, 6.1%) in Lafon. The presence of water and sanitation were low in all five counties, including two counties which had a complete absence of latrines in all surveyed clusters.To our knowledge, these were the first trachoma surveys conducted in the Republic of South Sudan since their independence in 2011. The results show that despite years of interventions, four of the five surveyed counties require a minimum of five additional years of SAFE strategy implementation, with the fifth requiring at minimum three more years.